Cognitive and motor improvement by tummy time practice in preemies from low-income settings: a randomized clinical trial - Sampaio, Sabrinne Suelen Santos; Amorim Rodrigues, Nathalia Allana; Souza, Thalyson Luiz Gomes; Moura, Julia Raffin; Azevedo, Ingrid Guerra; Lima-Alvarez, Carolina Daniel; Pereira, Silvana Alves (Frontiers in Psychology, 2024)
Introduction Early intervention and parental education for preemies are limited in some low-income countries. Thus, this study aimed to assess whether daily tummy time (TT) associated with usual care (UC) enhances motor and cognitive development in preemies from low-income countries. The main and secondary aim was to assess prone head elevation (PHE) and motor and cognitive functions, respectively. Methods Thirty-one preemies with a mean gestational age at birth of 33.3 ± 1.6 weeks and weighing <2,500 g were included and 18 completed all assessments. Parents from the TT group were asked to perform TT with their preemies for at least 20 min during daily activities and playtime. Motor and cognitive functions were assessed by a blinded examiner using the motor and cognitive composite scores of Bayley-III after two and four months of corrected age. PHE was given by the angle from the tragus of the ear to the supporting surface of the infant; measurements were obtained using the Kinovea® software at baseline, after two, three, and four months of corrected age. Results The Bayley-III motor composite score of the TT group was higher than the UC group after two and four months of corrected age. The PHE angle increased over time but did not differ between groups. Discussion Nevertheless, TT expanded the perspective of preemies to explore their bodies and environment, favoring the stimuli for motor and cognitive patterns. The loss of participants (31%) was one of the limitations of the study, illustrating the challenge of providing continued early interventions to preemies from low-income countries. In this sense, TT practice is a home intervention that may improve motor and cognitive function of preemies immediately after hospital discharge.